MICROINJECTION OF ANGIOTENSIN II IN THE CAUDAL VENTROLATERAL MEDULLA INDUCES HYPERALGESIA - Marques Lopes, J (2009)
Nociceptive transmission from the spinal cord is controlled by supraspinal pain modulating systems that include the caudal ventrolateral medulla (CVLM). The neuropeptide angiotensin II (Ang II) has multiple effects in the CNS and at the medulla oblongata. Here we evaluated the expression of angiotensin type 1 (AT(1)) receptors in spinally-projecting CVLM neurons, and tested the effect of direct application of exogenous Ang II in the CVLM on nociceptive behaviors. Although AT(1)-immunoreactive neurons occurred in the CVLM, only 3% of AT(1)-positive neurons were found to project to the dorsal horn, using double-immunodetection of the retrograde tracer cholera toxin subunit B. In behavioral studies, administration of Ang II (100 pmol) In the CVLM gave rise to hyperalgesia in both the tail-flick and formalin tests. This hyperalgesia was significantly attenuated by local administration of the AT(1) antagonist losartan. The present study demonstrates that Ang II can act on AT(1) receptors in the CVLM to modulate nociception. The effect on spinal nociceptive processing is likely indirect, since few AT(1)-expressing CVLM neurons were found to project to the spinal cord. The renin-angiotensin system may also play a role in other supraspinal areas Implicated in pain modulation.